Design and analysis of compact dictionaries for diagnosis in scan-BIST. - Chunsheng Liu (IEEE Transactions on VLSI systems)
We present a new technique for generating compact dictionaries for cause-effect diagnosis in scan-BIST. This approach relies on the use of three compact dictionaries and target both modeled and unmodeled faults. We present analytical results that provide useful guidelines for the design of these compact dictionaries. We also present experimental results for the larger ISCAS-89 benchmark circuits for the diagnosis of various types of unmodeled faults.